Design and Synthesis of Axial‐Chirality‐Containing Guanidine Catalysts. Issue 41 (2nd November 2022) - Iwakura, Manaya; Ikeue, Takahisa; Nakata, Kenya
Abstract: In this study, novel axial‐chirality‐containing guanidine catalysts were designed and synthesized, and their catalytic ability was systematically evaluated. In the presence of only 0.5 mol % catalytic loading, the catalysts were found to act efficiently in the silylative kinetic resolution of racemic 1‐indanols. Furthermore, a variety of substrates were applicable for the reaction with good‐to‐high s ‐values. Abstract : Novel axial‐chirality‐containing guanidine catalysts were designed and synthesized. The catalysts were used for the silylative kinetic resolution of racemic 1‐indanols, and it was found that various substrates were applicable for the reaction with high s ‐values using only 0.5 mol % of the catalyst loading.